Titanium nitride cleaning agent with low galvanic corrosion as well as preparation method and application of titanium nitride cleaning agent
Through a titanium nitride cleaning agent containing multiple specific components, the problems of galvanic corrosion between copper and tantalum and the removal of titanium nitride hard mask are solved, and low galvanic corrosion and selective cleaning are achieved, which is suitable for cleaning and industrial applications of semiconductor chips.
Patent Information
- Application Number
- CN202411675181.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-07
AI Technical Summary
In the prior art, there is a serious galvanic corrosion problem between copper and tantalum, and it is difficult to selectively remove the titanium nitride hard mask.
It provides a low-galvanized titanium nitride cleaning agent containing functional agents, antistatic agents, protective agents, organic alkalis, oxidants, solvents and ultrapure water. Through a pure immersion process, selective removal of titanium nitride and reducing galvanized corrosion of copper and tantalum without ultrasonic conditions are achieved.
Without ultrasonic waves, this cleaning agent can effectively remove titanium nitride, reduce galvanic corrosion between copper and tantalum, ensure the normal operation of the device, and be environmentally friendly and pollution-free, and is suitable for large-scale industrial promotion.
Smart Images

Figure CN119570577A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of semiconductor manufacturing technology, and in particular relates to a titanium nitride cleaning agent with low galvanic corrosion, a preparation method and application thereof. Background Art
[0002] With the development of semiconductor technology, the integration level of ultra-large-scale integration (ULSI) has reached the scale of hundreds of millions to billions of devices on a chip, and two or more layers of metal interconnects have been widely used. Traditional interconnects are made of aluminum. However, as the critical dimensions of semiconductor devices in integrated circuits continue to shrink, the circuit density of metal interconnects continues to increase; and the required response time continues to shorten, so traditional aluminum metal interconnects cannot meet the requirements of ULSI development. After the technology node is below 130nm, copper interconnects replaced aluminum interconnects. Compared with aluminum interconnects, copper has a lower resistivity, which can reduce the resistance-capacitance (RC) delay of the interconnect line, thereby improving electromigration; and the stability of the device may be improved. The most advanced method for forming copper metal interconnects is the embedding technology of the Damascus process.
[0003] With the development of semiconductor technology, in order to further reduce the resistance and capacitance delay effect of the back-end, it is necessary to combine the Damascus process and ultra-low K dielectric materials and introduce them into integrated circuit manufacturing. However, copper atoms can easily diffuse in dielectric materials, resulting in device failure, and copper has poor wettability to dielectric materials, so it is necessary to deposit a barrier layer on the sidewalls and bottom of the interconnect structure formed by the Damascus process. After that, copper metal is filled in the interconnect structure. After the integrated etching of the Damascus process, fluorine- and chlorine-containing polymers will remain on the inner wall of the through hole formed in the interlayer dielectric layer. Before depositing the barrier layer, wet cleaning is required to remove the polymer residues generated by the integrated etching. Before wet cleaning, there is static electricity on the surface of the wafer, which is induced by the plasma generated by the integrated etching. The static electricity causes the wet cleaning to be unable to effectively remove the polymer residues generated by the integrated etching, and a large amount of static electricity will exist at the polymer residues.
[0004] The mainstream barrier layer materials used in metal interconnect structures are tantalum (Ta) and tantalum nitride (TaN), which are usually tens of nanometers thick. Due to the presence of the above-mentioned electrostatic charge, electrocouple corrosion will be induced at the interface where tantalum and copper contact, causing corrosion of copper metal. When the device's anti-static ability deteriorates, copper metal corrosion is more likely to occur, resulting in a decrease in device performance.
[0005] The purpose of the present application is to provide a cleaning agent for improving the galvanic corrosion of copper metal interconnects, which is used to solve the problem of galvanic corrosion between copper in the copper interconnect structure and tantalum in the barrier layer in the prior art. At the same time, the cleaning agent can selectively remove a certain thickness of titanium nitride hard mask. Summary of the invention
[0006] The technical problem solved by the present invention is to solve the problem that the copper and tantalum galvanic corrosion is serious and the titanium nitride hard mask cannot be selectively removed.
[0007] In view of the technical problems existing in the prior art, the present invention provides a titanium nitride cleaning agent with low galvanic corrosion, a preparation method and use thereof, which can maintain extremely excellent selectivity and low corrosion potential only under pure immersion process conditions without the need for ultrasonic cleaning.
[0008] It should be noted that, in the present invention, unless otherwise specified, the specific meaning of "including" in relation to composition limitations and descriptions includes both open-ended "including", "comprising" and similar meanings, and closed-ended "consisting of..." and similar meanings.
[0009] In order to solve the above-mentioned technical problems, the present invention adopts the following solutions:
[0010] A low galvanic corrosion titanium nitride cleaning agent, characterized in that it comprises the following components calculated by weight:
[0011] Functional agent 12-20 parts;
[0012] 1-7 parts of antistatic agent;
[0013] Protective agent 0.2-1 part;
[0014] 6-13 parts of organic base;
[0015] 3-14 parts of oxidant;
[0016] 15-25 parts of solvent;
[0017] 40-60 parts of ultrapure water.
[0018] Furthermore, the functional agent is at least one of 1-octyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide salt (CAS No.: 862731-66-6), 1-dodecyl-3-methylimidazolium tetrafluoroborate, and 1-butyl-3-methylimidazolium n-alkylsulfonate.
[0019] Furthermore, the antistatic agent is at least one of diaminophosphophenyl ester, fatty alcohol phosphate, fatty alcohol polyoxyethylene ether phosphate, and polyoxyethylene laurate.
[0020] Furthermore, the protective agent is at least one of sodium benzotriazole, benzotriazole, 2-mercaptobenzothiazole, sodium mercaptobenzothiazole, and methylbenzotriazole.
[0021] Furthermore, the organic base is at least one of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, diethanolamine, triethanolamine, propanolamine, N,N,N,N,N-pentamethyldivinyltriamine and N,N,N,N-tetramethyl-1,6-hexanediamine.
[0022] Furthermore, the oxidant is at least one of hydrogen peroxide, dibenzoyl peroxide, peracetic acid, urea peroxide, perbenzoic acid, ammonium persulfate, perbenzoic acid, periodic acid, perchloric acid, and N-methylmorpholine oxide.
[0023] Furthermore, the solvent is at least one of ethanol, glycerol, isopropanol, isohexylene glycol, diethylene glycol, propylene glycol methyl ether, dipropylene glycol butyl ether, and ethyl acetate.
[0024] The present invention also discloses a method for preparing a titanium nitride cleaning agent with low galvanic corrosion, which is characterized by comprising the following steps:
[0025] Step 1: Weigh each component in its respective amount;
[0026] Step 2: Add ultrapure water and solvent into a container, add functional agent, antistatic agent and protective agent under stirring, after all materials are completely dissolved, add organic base and oxidant successively under stirring, stir until uniform, and obtain the cleaning agent.
[0027] The present invention also discloses a method for using a titanium nitride cleaning agent with low galvanic corrosion, which is characterized by comprising the following steps:
[0028] Step 1: preparing the cleaning agent with ultrapure water into an aqueous solution with a mass percentage concentration of 60-85%, and then using the aqueous solution to soak the semiconductor chip at 20-40° C. for 5-15 minutes to obtain a soaked semiconductor chip;
[0029] Step 2: Rinse the soaked semiconductor chip in ultrapure water at least twice, thereby completing the cleaning process of the semiconductor chip.
[0030] The invention also discloses the use of a titanium nitride cleaning agent with low galvanic corrosion in cleaning titanium nitride chips.
[0031] In the cleaning agent system of the present invention, in order to further optimize the effect, each component can be optimized, functional agent 15-19 parts; antistatic agent 2-5 parts; protective agent 0.4-0.8 parts; organic base 8-11 parts; oxidant 5-12 parts; solvent 18-22 parts; ultrapure water 45-55 parts.
[0032] In the present invention, the functional agent is preferably 1-octyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide salt.
[0033] In the present invention, the antistatic agent is preferably phenyl diaminophosphorate.
[0034] In the present invention, the protective agent is preferably tolyltriazole.
[0035] In the present invention, the organic base is preferably diethanolamine.
[0036] In the present invention, the oxidizing agent is preferably hydrogen peroxide.
[0037] In the present invention, the solvent is preferably diethylene glycol.
[0038] In the present invention, the functional agent and the antistatic agent have special effects:
[0039] The combination of functional agent and antistatic agent has the dual functions of etching and reducing the electrostatic charge on the wafer surface. Its etching function can quickly remove titanium nitride. At the same time, the combination of functional agent and antistatic agent can reduce the potential difference between the cleaning agent and the wafer surface, prevent static electricity accumulation, further reduce the galvanic potential of copper and tantalum, and reduce copper corrosion; the functional agent can also provide fluoride ions to avoid the use of hydrofluoric acid and cause adverse effects on the environment and instruments.
[0040] In the present invention, the protective agent has a unique effect:
[0041] The protective agent forms a complex with copper ions and forms a film on the copper surface by chemical adsorption, which effectively reduces the corrosion of copper by the cleaning agent during the cleaning process. Combined with the functional agent's early elimination of electrostatic charge on the wafer surface, the galvanic potential of copper and tantalum is greatly reduced.
[0042] The present invention provides a titanium nitride cleaning agent with low galvanic corrosion and a preparation method and use thereof, which have the following beneficial effects:
[0043] 1. The present invention uses a functional agent, which has a higher etching rate for titanium nitride and a lower corrosion rate for non-metals (such as LP-TEOS, BD II, Si3N4, etc.); and has a good improvement effect on the corrosion potential difference between Cu and Ta, reducing the potential difference between the two, so as to avoid galvanic corrosion during the cleaning process and ensure the normal operation of the device.
[0044] 2. The cleaning agent of the present invention is environmentally friendly, pollution-free, and has low volatile loss. After cleaning, there is no need to use acetone for rinsing, and only pure water is needed for rinsing, which is harmless to the environment and human body.
[0045] Therefore, the cleaning agent of the present invention has very good application prospects and large-scale industrial promotion potential in the field of semiconductor chip cleaning. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1: is the Cu-Ta polarization curve of comparative example 2;
[0047] Figure 2 : This is the Cu-Ta polarization curve diagram of Example 1. DETAILED DESCRIPTION
[0048] The present invention will be further described below in conjunction with specific embodiments and accompanying drawings:
[0049] Table 1 Examples 1-8
[0050]
[0051]
[0052] Table 2 Comparative Examples 1-3
[0053]
[0054] Table 3 Test data
[0055]
[0056]
[0057] The preparation method of the titanium nitride cleaning agent of the present invention comprises the following steps:
[0058] Step 1: Weigh each component in its respective amount;
[0059] Step 2: Add ultrapure water and solvent into a container, add functional agent, antistatic agent and protective agent under stirring, after all materials are completely dissolved, add organic base and oxidant successively under stirring, stir until uniform, and obtain the cleaning agent.
[0060] The method for using the titanium nitride cleaning agent of the present invention comprises the following steps:
[0061] Step 1: preparing the cleaning agent with ultrapure water into an aqueous solution with a mass percentage concentration of 80%, and then using the aqueous solution to soak the semiconductor chip at 35° C. for 6 minutes to obtain a soaked semiconductor chip;
[0062] Step 2: Rinse the soaked semiconductor chip in ultrapure water at least twice, thereby completing the cleaning process of the semiconductor chip.
[0063] About performance testing and description:
[0064] Performance 1 The test method for metal corrosion is:
[0065] The mini-SWT method was used to test the corrosion performance of the cleaning agent on metals. A 2cm×2cm copper wafer, a tantalum wafer, and a titanium nitride wafer were placed on the single-chip machine table. After the cleaning agent temperature reached 20-40°C, spraying was performed for 10 minutes. Then, a four-point probe was used to measure the film thickness (the metal pre-value film thickness was measured before spraying) and the metal corrosion rate was calculated (the pre-value film thickness minus the post-value film thickness, the difference was divided by the spraying time, and the metal corrosion rate was obtained). Right now / minute, also known as "etching rate"), thereby examining the corrosion rate of the cleaning agent on the metal.
[0066] Performance 2 The test method for non-metallic corrosion is:
[0067] A 2cm×2cm non-metallic wafer was sprayed in the mini-SWT for 10 minutes (similarly, the cleaning agent temperature must be waited until 20-40°C), and the film thickness of the non-metallic wafer before and after spraying was measured to calculate its corrosion rate.
[0068] Performance 3 The test method of Cu-Ta potential difference is:
[0069] The Cu and Ta corrosion was carried out by electrochemical workstation. The specific steps are as follows:
[0070] Step 1: After grinding the Cu / Ta electrode with sandpaper, polish the electrode surface with polishing paste; then place the electrode in an ethanol solution for ultrasonic treatment for 10 minutes; after the ultrasonic treatment, rinse the electrode with ultrapure water and then blow dry with nitrogen;
[0071] Step 2: Immerse the treated electrode together with the counter electrode and the reference electrode in a cleaning agent to measure the open circuit voltage and polarization curve of Cu / Ta;
[0072] Step 3: Fit the obtained Cu / Ta polarization curve to obtain the Cu-Ta potential difference.
[0073] The ultrapure water used in the above steps is deionized water with a resistance of at least 18M.
[0074] Analysis of the test results:
[0075] It can be seen from the test data in Table 3 that adding a functional agent can quickly and effectively remove titanium nitride; adding an electrostatic agent can effectively reduce the Cu-Ta potential difference, but the ability to remove titanium nitride is average; and the embodiment after combining the two additions achieves the effect of quickly removing titanium nitride and reducing the Cu-Ta potential difference, further reducing galvanic corrosion.
[0076] Further comparison is made through the attached drawings in the specification:
[0077] Figure 1 It is the Cu-Ta polarization curve diagram of comparative example 2; Figure 2 This is the Cu-Ta polarization curve of Example 1.
[0078] from Figure 1 and Figure 2 It can be seen from the comparison that the titanium nitride cleaning agent prepared in Example 1 of the present invention can effectively improve the Cu-Ta potential difference, prevent static electricity accumulation, and reduce copper corrosion. It can be clearly seen from the figure that the potential difference between Cu and Ta is reduced. However, the Cu-Ta potential difference of the cleaning agent in Comparative Example 2 is larger.
[0079] The present invention is described exemplarily above in conjunction with the embodiments and drawings. It is obvious that the implementation of the present invention is not limited to the above-mentioned methods. As long as various improvements are made using the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.
Claims
1. A titanium nitride cleaning agent with low galvanic corrosion, characterized in that: Calculated by weight, it includes the following components:
2. The low galvanic corrosion titanium nitride cleaning agent according to claim 1, characterized in that: The functional agent is at least one of 1-octyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide salt, 1-dodecyl-3-methylimidazolium tetrafluoroborate, and 1-butyl-3-methylimidazolium n-alkylsulfonate.
3. The low galvanic corrosion titanium nitride cleaning agent according to claim 1, characterized in that: The antistatic agent is at least one of diamino phenyl phosphate, fatty alcohol phosphate, fatty alcohol polyoxyethylene ether phosphate, and polyoxyethylene laurate.
4. The low galvanic corrosion titanium nitride cleaning agent according to claim 1, characterized in that: The protective agent is at least one of sodium benzotriazole, benzotriazole, 2-mercaptobenzothiazole, sodium mercaptobenzothiazole and methylbenzotriazole.
5. The low galvanic corrosion titanium nitride cleaning agent according to claim 1, characterized in that: The organic base is at least one of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, diethanolamine, triethanolamine, propanolamine, N,N,N,N,N-pentamethyldiethylenetriamine and N,N,N,N-tetramethyl-1,6-hexanediamine.
6. The low galvanic corrosion titanium nitride cleaning agent according to claim 1, characterized in that: The oxidant is at least one of hydrogen peroxide, dibenzoyl peroxide, peracetic acid, urea peroxide, perbenzoic acid, ammonium persulfate, perbenzoic acid, periodic acid, perchloric acid, and N-methylmorpholine oxide.
7. The low galvanic corrosion titanium nitride cleaning agent according to claim 1, characterized in that: The solvent is at least one of ethanol, glycerol, isopropanol, isohexylene glycol, diethylene glycol, propylene glycol methyl ether, dipropylene glycol butyl ether and ethyl acetate.
8. A method for preparing the low galvanic corrosion titanium nitride cleaning agent according to any one of claims 1 to 7, characterized in that The steps include: Step 1: Weigh the respective amounts of each component; Step 2: Add ultrapure water and solvent into a container, add functional agent, antistatic agent and protective agent under stirring, after all materials are completely dissolved, add organic base and oxidant successively under stirring, stir until uniform, and obtain the cleaning agent.
9. A method for using a low galvanic corrosion titanium nitride cleaning agent, characterized in that The following steps are involved: Step 1: preparing the cleaning agent with ultrapure water into an aqueous solution with a mass percentage concentration of 60-85%, and then using the aqueous solution to soak the semiconductor chip at 20-40° C. for 5-15 minutes to obtain a soaked semiconductor chip; Step 2: Rinse the soaked semiconductor chip in ultrapure water at least twice, thereby completing the cleaning process of the semiconductor chip.
10. Use of the titanium nitride cleaning agent with low galvanic corrosion according to any one of claims 1 to 7 in cleaning titanium nitride chips.